Pemanfaatan Alam Sekitar Sebagai Sumber Belajar Mata Pelajaran IPA di Madrasah Ibtidaiyah - Fauzi, Fauzi (Pusat Studi Pendidikan Kreatifitas Anak Wadas Kelir Purwokerto, 2020)
The purpose of this study is to describe the use of natural surroundings as a source of learning science subjects. To explore this, a study was conducted using a qualitative approach. In this case, the subject of the study was one of the students who supported the subject who became the class teacher in class V, with a total of 28 students. The method used in data collection is the method of observation, documentation and interviews. To complete the accuracy of the research and the validity of the data it is necessary to use research methods and techniques in order to obtain maximum results. The results obtained from the study are: Utilization of the surrounding environment is a vehicle that can be used as a source of learning that is done in the form of variety and fun when the learning process takes place both in the classroom and outside the classroom. School parks, gardens, and rice fields that are nearby can be used as a source of interesting and fun learning. In implementing the use of the environment as a source of learning, there are obstacles between the lack of an educator's ability to condition learners, which requires a significant amount of time in the implementation process, students feel confused in reviewing the results of activities, and learning resources that are less accommodating.